2020
DOI: 10.1016/j.ejvs.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Drug Coated Balloon Angioplasty vs. Standard Percutaneous Transluminal Angioplasty in Below the Knee Peripheral Arterial Disease: A Systematic Review and Meta-Analysis

Abstract: WHAT THIS PAPER ADDS This systematic review and meta-analysis is an update on the role of drug coated balloons in the endovascular treatment of infrapopliteal arterial disease. Based on the results of this paper no statistically significant differences were found between drug coated balloon angioplasty and standard percutaneous transluminal angioplasty. Objective: The aim was to review and analyse the literature on clinical outcomes of drug coated balloon (DCB) vs. standard percutaneous transluminal angioplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…The lack of clear benefit of PCB has since then been confirmed by Ipema et al [67] in their review of 10 studies including 1593 patients. The authors did not reveal a significant difference in their primary outcomes of 12-month limb salvage or secondary endpoints (survival, restenosis, TLR, amputation-free survival).…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 88%
“…The lack of clear benefit of PCB has since then been confirmed by Ipema et al [67] in their review of 10 studies including 1593 patients. The authors did not reveal a significant difference in their primary outcomes of 12-month limb salvage or secondary endpoints (survival, restenosis, TLR, amputation-free survival).…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 88%
“… 29 However, there are other meta-analyses that did not show superiority of PCB over CBA in terms of binary restenosis, TLR, and major amputation rates. 30 32 Furthermore, Katsanos et al 15 have recently showed a worse 1-year AFS rate following infrapopliteal arteries treated with PCBs, although this meta-analysis has been heavily criticized for use of nonpublished data at the time. AFS was worse in those studies using a higher dose (3.0–3.5 µg/mm 2 ) balloon drug coating and paclitaxel distal embolization was postulated to be the underlying mechanism by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason why there may have been a discrepancy in different meta-analysis findings in the efficacy of PCBs in the tibial vessels may be related to adequacy of lesion preparation between the studies included. 32 Literature describes favorable outcomes for prolonged inflation time especially for more calcified and long total occlusive lesions. 34 , 35 In PRESTIGE, both primary investigators used a 180-second preparatory CBA inflation time and judicial use of longer length balloons to minimize the risk of dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Would this have improved the primary patency of 73% at 6 months? Data using paclitaxel coated balloons (PCB) in tibial lesions are currently conflictory with a recent metaanalysis showing no advantage in terms of limb salvage, survival, restenosis and TLR over POBA [10]. Furthermore safety concerns have been raised recently using PCB below the knee by Katsanos et al who showed a worse one-year AFS rate (a composite endpoint of death and major LEA) following treatment of infra-popliteal arteries with PCBs [11], although this was not borne out from a subsequent meta-analysis by Dinh et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Devices coated with paclitaxel have been used successfully in the clinical arena to limit restenosis by inhibiting the biologic pathway that leads to NIH [9]. However, recent systematic reviews and study-level meta-analyses of randomized controlled trials investigating treatment of the infra-popliteal arteries with paclitaxel-coated balloons (PCB) compared with conventional POBA for CLTI either showed no significant differences in limb salvage, survival, restenosis, TLR, and amputation-free survival (AFS) between the two groups [10] or was significantly worse in those who had PCB [11]. Current poor patency seen in tibial angioplasty is also likely contributed in part by small vessel size, especially pertinent to Asian tibial arteries, and poor luminal gain after standard semi-compliant POBA.…”
Section: Introductionmentioning
confidence: 99%